Implementasi Game Edukasi Pengenalan Budaya Bangka Belitung untuk Anak SD (Studi Kasus : SDN 13 KOBA) - Sonya, Sonya; Andriyanto, Sidhiq; Fujiyanti, Linda (Jurnal Inovasi Teknologi Terapan, 2024)
Bangka Belitung is an area that has a variety of cultures. However, as time goes by, especially children at elementary school are less exposed to local culture. Due to the limited availability of instructional tools or learning media to practice the existing material, especially in the current era where the use of gadgets among children is increasing; however, these gadgets are predominantly utilized for playing non-educational games. Therefore, learning media is needed as a bridge to introduce local culture in order to increase children's knowledge and maintain the culture. The media that is suitable to overcome this problem is an Android-based educational game that introduces Bangka Belitung's culture. The method used in developing is GDLC (Game Development Life Cycle). This method has six stages, namely initiation, pre-production, production, testing (alpha), testing (beta) and release. With white box and black box testing, it's obtained that according to white box results that it is very good for use and according to black box method of user acceptance testing, test from the teachers obtained a percentage of 100% and for students 93.55% which means it is very suitable for use.